Retiree Health Insurance for Public School Employees: Does it Affect Retirement? - Maria D. Fitzpatrick (Center for Economic Studies and ifo Institute (CESifo), 2013)
Despite the widespread provision of retiree health insurance for public sector workers, little attention has been paid to its effects on employee retirement. This is in contrast to the large literature on health-insurance-induced job-lock in the private sector. I use the introduction of retiree health insurance for public school employees in combination with administrative data on their retirement to identify the effects of retiree health insurance. As expected, the availability of retiree health insurance for older workers allows employees to retire earlier. These behavioral changes have budgetary implications, likely making the programs self-financing rather than costly to taxpayers.
Keywords: J26; H75; I28; I21; 330; retirement; health insurance; public sector employment; teacher labor supply